Evaluating distributions of economic impacts of FMD emergency strategies in the United States - Ajewole, Kayode Martins (Kansas State University, 2013)
The livestock industry is susceptible to several diseases, of which Foot and Mouth Disease (FMD) is one. FMD is neither a fatal nor zoonotic animal disease, but most animals less than one year of age are killed in about 80% of cases. FMD also causes reductions in yield and milk production. FMD is recognized as an economic disease because any outbreak will lead to a drastic reduction in the export market. This study is centered on livestock production in mid-western United States. The study incorporated the result from an epidemiology model into an equilibrium displacement model; this is used to determine the economic impact of the FMD outbreak on both consumers and producers. Three vaccination-to-die scenarios were simulated. Each scenario had 200 disease spread simulation runs. The economic impact results were presented with normal distribution curves in order to see how the economic impacts were distributed across the 200 runs in each scenario. Scenario 14 with 50 and 80 herds vaccination capacity at 22 and 40 days respectively, coupled with 50 km vaccination zone has the lowest negative impact on both consumer and producers. The diseases lasted for shorter period of time in scenario 14 than scenarios 2 and 12. Scenario 14 also has least number of animals killed. It can be concluded from the equilibrium displacement outcomes that the best mitigation strategy for the control of FMD is to have a large vaccination zone area, and increment in the vaccination capacity will also curb the disease on time.
Keywords: Foot and Mouth Disease; Economic impact; Distribution; Economics, Agricultural (0503)